Faktor-faktor yang berhubungan dengan wasting pada Balita di Puskesmas Awal Terusan kec. SP Padang Kab. Ogan Komering Ilir Tahun 2023 - Anggerayani, Eftri; rohaya, rohaya; Afrika, Eka (NHM PRESS, 2023)
According toUnited Nations International Children's Emergency Fund (UNICEF) predicts 2020 eventswasting in children under the age of 5 years it is estimated as many as 38.2 million.Wasting that occurs in children under five can be caused by several factors. Causative factorwasting including nutritional intake, exclusive breastfeeding, completeness of immunization, infectious diseases, economic level, knowledge, education, mother's occupation. The purpose of this study to determine the factors associated withWasting in Toddlers at the Awal Terusan Health Center, Sirah Pulau Padang District, Kab. Ogan Komering Ilir Year 2023. The research design usesanalytical survey with approachcross sectional. The population in this study were all toddlers aged 24–60 months in the working area of the Awal Terusan Health Center, Sirah Pulau Padang District, Kab. OIC totaling 277 people. The sampling technique in this study was carried out by:accidental sampling with a total sample of 73 respondents. Collecting data using a questionnaire sheet. Data analysis using univariate analysis and bivariate analysis using testwho squares.The results of the study there is a relationship with a history of exclusive breastfeeding(p value = 0.049), history of immunization completeness(p value = 0.039), knowledge(p value = 0,014) and family income(p value = 0.004) withwasting in toddlers at Awal Terusan Health Center, Sirah Pulau Padang District, Kab. OKI in 2023. It is hoped that the results of this research can be an illustration for the puskesmas to be able to increase public knowledge aboutwasting in toddlers such as by providing regular counseling to the field.